2016
DOI: 10.4103/1117-1936.196265
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cleaning ability of three nickel-titanium rotary systems: ProTaper universal, K3 and Mtwo: An in vitro scanning electron microscopic study

Abstract: There was no statistically significant difference between the three tested groups - ProTaper, K3 and Mtwo in cleaning different regions of the canal - coronal, middle and apical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
2
0
4
Order By: Relevance
“…The standardization of canal length varied among the published literature. Root canal length and depth of insertion of irrigation needle have an effect on the efficacy of irrigant to remove the debris from the canal [ 40 ], and cleaning of the apical third of the canal has always been challenging compared to coronal and middle third [ 41 ]. This can be due to the formation of the vapor lock phenomenon at the apical third, as the root is a closed-ended channel being surrounded by periodontium [ 42 43 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standardization of canal length varied among the published literature. Root canal length and depth of insertion of irrigation needle have an effect on the efficacy of irrigant to remove the debris from the canal [ 40 ], and cleaning of the apical third of the canal has always been challenging compared to coronal and middle third [ 41 ]. This can be due to the formation of the vapor lock phenomenon at the apical third, as the root is a closed-ended channel being surrounded by periodontium [ 42 43 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different endodontic file systems produce different amounts of debris within the root canal system [ 57 58 ]. However, it is to be noted that studies have reported no significant difference in debris and smear layer formation in the root canal system prepared by ProTaper and MTwo rotary system [ 59 60 ] and between ProTaper, K3 nickel-titanium and MTwo rotary system [ 41 ]. Therefore, it can be inferred that the rotary system does not have a huge impact on the evaluation of smear layer removal of irrigants despite various endodontic file systems employed in the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…O tempo médio de preparo para LS, PT e Ew foi de 1,76, 2,50 e 2,75, respectivamente. Raut et al, (2016) compararam a eficácia da limpeza do preparo do canal em 36 raízes mésio-vestibular de três diferentes sistemas rotatórios de NiTi, ProTaper Universal, K3 e Mtwo, em microscopia eletrônica de varredura em quatro grupos: ProTaper Universal, K3, sistema Mtwo e grupo controle. O irrigante usado após cada instrumento foi 3 mL de hipoclorito de sódio a 3%.…”
Section: Introductionunclassified
“…Relativamente à utilização de substratos plásticos é evidente em pesquisas na endodontia, sobretudo, na instrumentação de canais. Diversos substratos são empregados em várias investigações com vistas a pesquisar a capacidade e eficiência de corte de instrumentos endodônticos destacando-se entre outros, dentes naturais humanos extraídos (Morrison et al 1989;Schäfer et al, 2006b;Zollner et al, 2007;Zago et al, 2013;Cumbo et al, 2015;Hema et al, 2015;Raut et al, 2016;Baxter et al, 2019) e há aqueles que usam materiais sintéticos resinosos (Morrison et al, 1989;Borges 2005;Schäfer et al, 2006a;Alkmin et al, 2007;Alves-Claro et al, 2008;Mansano 2009;Haddad et al, 2011;Reis et al, 2011;Medeiros et al, 2012;Salum 2012;Arantes et al, 2014;Medeiros et al, 2022) dispositivo de aço inoxidável utilizado em função de tempo e número de ciclos de fratura (Tanomaru-Filho et al, 2018), presença ou não de resíduos nos instrumentos antes do primeiro uso (Medeiros et al, 2019).…”
unclassified
See 1 more Smart Citation